Ciprofloxacin removal from non-clinical environment: A critical review of current methods and future trend prospects - Al-Buriahi, Abdullah Khaled; M. Al-shaibani, Muhanna; Radin Mohamed, Radin Maya Saphira; Al-Gheethi, Adel Ali; Sharma, Ajit; Ismail, Norli (Elsevier, 2022)
Antibiotics in the environment represent a significant threat to global public health. Ciprofloxacin (CIP) is one of the second generation groups of synthetic fluoroquinolones and the most widely used antibiotics worldwide. The current work aimed to review and analyze the current methods used for eliminating CIP and identify the approaches for more advanced technologies that could provide more removal efficiency for CIP removal from the non-clinical environment. The VOSviewer software tool was used to build and visualize bibliometric networks by creating a map based on bibliographic data for keywords and most countries published on the CIP removal from the Scopus database. The present review analyses the sustainable methods for removing CIP from the non-clinical environment and highlights the most efficient techniques used to remove CIP. The adsorption process of CIP is highly efficient, with a removal percentage of 95%. The microbial electrolysis ultraviolet cell (MEUC) procedure removed 100% of CIP. The degradation of CIP by UV/H2O2/O3 and its sub-processes increased the degradation of CIP from 41.2% to 98.5%. The photocatalytic degradation exhibit 92.81% removal of CIP from wastewater samples. The three-dimensional (3D) porous graphene has excellent adsorption properties to eliminate CIP by 93% in water purification. Each method has advantages and disadvantages based on price, time and presence of toxic by-products. This review is expected to serve as a base for recent research and assist researchers in developing alternative CIP treatment approaches with more efficient removal methods.